The Caenorhabditis elegans GATA factor ELT-1 works through the cell proliferation regulator BRO-1 and the Fusogen EFF-1 to maintain the seam stem-like fate. - Brabin, C; Appleford, P; Woollard, A (Public Library of Science, 2011)
Seam cells in Caenorhabditis elegans provide a paradigm for the stem cell mode of division, with the ability to both self-renew and produce daughters that differentiate. The transcription factor RNT-1 and its DNA binding partner BRO-1 (homologues of the mammalian cancer-associated stem cell regulators RUNX and CBFandbeta;, respectively) are known rate-limiting regulators of seam cell proliferation. Here, we show, using a combination of comparative genomics and DNA binding assays, that bro-1 expression is directly regulated by the GATA factor ELT-1. elt-1(RNAi) animals display similar seam cell lineage defects to bro-1 mutants, but have an additional phenotype in which seam cells lose their stem cell-like properties and differentiate inappropriately by fusing with the hyp7 epidermal syncytium. This phenotype is dependent on the fusogen EFF-1, which we show is repressed by ELT-1 in seam cells. Overall, our data suggest that ELT-1 has dual roles in the stem-like seam cells, acting both to promote proliferation and prevent differentiation.